Decolonizing History: Enquiry and Practice. (17th February 2020) - Behm, Amanda; Fryar, Christienna; Hunter, Emma; Leake, Elisabeth; Lewis, Su Lin; Miller-Davenport, Sarah
Abstract: On the back of the Royal Historical Society's 2018 report on race and ethnicity, as well as ongoing discussions about 'decolonizing the syllabus', this is a conversation piece titled, 'Decolonizing History: Enquiry and Practice'. While 'decolonization' has been a key framework for historical research, it has assumed increasingly varied and nebulous meanings in teaching, where calls for 'decolonizing' are largely divorced from the actual end of empire. How does 'decolonizing history' relate to the study of decolonization? And can history, as a field of practice and study, be 'decolonized' without directly taking up histories of empire? Using the RHS report as a starting point, this conversation explores how we 'decolonize history'. We argue that, rather than occurring through tokenism or the barest diversification of reading lists and course themes, decolonizing history requires rigorous critical study of empire, power and political contestation, alongside close reflection on constructed categories of social difference. Bringing together scholars from several UK universities whose teaching and research ranges across modern historical fields, this piece emphasizes how the study of empire and decolonization can bring a necessary global perspective to what tend to be framed as domestic debates on race, ethnicity, and gender.